I like killing flies [videorecording (DVD)] - Mahurin, Matt; Shopsin, Kenny; Shopsin, Eve (Docurama Films : Distributed by New Video Group, 2007)
With more than 900 items on its menu, all made from scratch in a tiny kitchen humming with improvised Rube Goldberg-like contraptions, Shopsin's has long been a quirky gem of New York food culture. Follows Kenny Shopsin, his family and customers as the restaurant looks for a new place to go.